The roles of mediators and moderators in the adoption of Madrasati (M) LMS among teachers in Riyadh - Alharbi, Hamad; Ab Jalil, Habibah; Omar, Muhd Khaizer; Mohd Puad, Mohd Hazwan (Society for Research and Knowledge Management, 2022)
This study aims to determine the mediators’ and moderators’ roles in the adoption of the Madrasati (M) learning management system (LMS) among teachers in Riyadh. This study used the survey approach; it and involved 374 teachers, that use M LMS to deliver their instructions. The study’s samples represent the larger population of 13,782 public school teachers in Riyadh; 413 responses were collected after distributing 500 questionnaires. The independent variables are performance-expectancy (PE), effort-expectancy (EE), social-influence (SI), and facilitating conditions (FC); while Madrasati (M) LMS utilisation is the dependent variable. Meanwhile, behavioural intention serves as a moderator variable, while age and gender functions serve as mediators. This study discovered that behavioural intention, age, and gender all play mediating or moderating roles in M LMS utilisation among Riyadh teachers. In terms of mediation variables, this study found that the links between PE, SI, and FC and M LMS utilisation are significantly mediated by behavioural intention. However, there is no evidence that BI plays a moderating role in the relationship between EE and M LMS. Regarding age, all age groups’ moderating effects on M LMS- utilisations showed significant beta values, except on PE, which is not significant. However, EE had a substantially moderating effect on M LMS usage for teachers aged 30 and younger and teachers aged 31–40, while the beta values for teachers aged 41–50, and 51 and above, were not significant. It is suggested that future research should consider other variables, such as years of experience, which could influence the link between the variables and other components.